(3GdYSLO GdefXe aj aVd GdEeGe GdeYXes - (3eMeO Hf CHi HcQ GdSMhdis
(3ChdgG (B:s
(3GdMeO ddg GdChd HdG EHJOGA , hGdBNQ HdG EfJgGA , hGdhGLO HdG fXjQ s
(3BNQgG (B:s
(3hHYO , agPG BNQ eG Sgd Gddg JYGdi fbdg ai aVd GdEeGe hYOdg hENJjGQg dCgd Ydeg heG dG Zfi Yf eYQaJg Je GdcJGH s
(3hgh cJGH ai GdSjGSI jHMK ai aVd GdEeGeI hYO dg hgjHJg hSjQJg hZjQ Pdcs
(3HBNQgG HebOGQ (B35 (3hQbI fUhU efbhdg dgG YdGbI HehVhY GdcJGHs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA s
Keywords: (3GdeYGQa GdYGeIs